2010
DOI: 10.1080/14786410902726134
|View full text |Cite
|
Sign up to set email alerts
|

Three new dioxopiperazine metabolites from a marine-derived fungus Aspergillus fumigatus Fres.

Abstract: Three new dioxopiperazine metabolites (1-3), together with two known compounds, N-acetyltyramine (4) and cyclo-(Ala-Val) (5), were isolated from a marine-derived fungus Aspergillus fumigatus Fres. Their structures were established by spectroscopic methods. Their cytotoxic activities against the K562 cell line were preliminarily evaluated by the sulphorhodamine B (SRB) method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…The study reported for the first time the bioactivity of a marine-derived A. fumigatus against T. congolense. Previous studies reported the isolation of A. fumigatus from macroalgae, sea sediment, and holothurians, and showed to produce several cytotoxic compounds such as N-acetyltyramine (Zhao et al 2010) and the apoptosis-inducing metabolite fumigaclavine C (Li et al 2013). Moreover, Furtado et al (2005) also reported that A. fumigatus derived from soil samples produced metabolites that are bioactive against T. cruzi, which causes Chagas disease.…”
Section: Marine Aspergillimentioning
confidence: 99%
“…The study reported for the first time the bioactivity of a marine-derived A. fumigatus against T. congolense. Previous studies reported the isolation of A. fumigatus from macroalgae, sea sediment, and holothurians, and showed to produce several cytotoxic compounds such as N-acetyltyramine (Zhao et al 2010) and the apoptosis-inducing metabolite fumigaclavine C (Li et al 2013). Moreover, Furtado et al (2005) also reported that A. fumigatus derived from soil samples produced metabolites that are bioactive against T. cruzi, which causes Chagas disease.…”
Section: Marine Aspergillimentioning
confidence: 99%
“…Marine fungi produce unique and biologically active secondary metabolites (Zhao et al 2010;Deng et al 2013;Suciati et al 2013). As part of our continuous study of the secondary metabolites from marine fungi, marine sponge samples were collected from the Xisha Islands of China.…”
Section: Introductionmentioning
confidence: 99%
“…The EtOAc extract was subjected to a series of solvent/solvent partitioning steps to afford compounds 1 – 12 (Figure 1). Three new structures were identified by the combination of spectroscopic analysis, high-resolution electrospray mass spectrometry (HRESIMS), and electronic circular dichroism (ECD) calculation, while twelve known analogues were identified as bisdethiobis (methylthio)gliotoxin ( 4 ) [10,11], 6-acetylbis(methylthio)gliotoxin ( 5 ) [9,12], 6-deoxy-5a,6-didehydrogliotoxin ( 6 ) [13], 5a,6-didehydrogliotoxin ( 7 ) [14], 6-(phenylmethyl)-(3 R ,6 R )-2,5-piperazinedione ( 8 ) [15], 3-(hydroxymethyl)-3,6-bis(methylthio)-6-(phenylmethyl)-(3 R ,6 R )-2,5-piperazinedione ( 9 ) [15], 3-(hydroxymethyl)-6-(methoxyl)-6-(phenylmethyl)-(3 R ,6 R )-2,5-piperazinedione ( 10 ) [16], 5a,6-anhydrobisdethiobis(methylthio)gliotoxin ( 11 ) [17], and bisdethiobis (methylthio)gliotoxin ( 12 ) [12] by comparison of their spectroscopic data with those in the literature.…”
Section: Resultsmentioning
confidence: 99%